Think Like a Marketer - Colbert, Kate (Ascent Audio, 2019)
The Secret to Taking Your Business from Mediocre to Meaningfully Different? Thinking like a marketer. It's also the secret to moving your organization from status quo to success story, and from busy to profitable. In an accessible, practical new guidebook, acclaimed marketing expert Kate Colbert offers fresh insights into the actions and attitudes that can accelerate your business success, sharpen your daily work, and balance your efforts to create value for customers while capturing value for the bottom line. For non-marketers and marketers alike, truly thinking like a marketer requires the right framework, and this book is everything you need to make the mindset shift that can change everything for your business.